Chloroquine maculopathy in a patient on long-term chloroquine therapy for pulmonary sarcoidosis: a case report (Ukrainian Journal of Ophthalmology, 2025)
The article is on an important subject, chloroquine maculopathy associated with long-term use of chloroquine. Given that chloroquine has been widely used for the treatment of COVID-19, it is important to accumulate data on adverse reaction to chloroquine and its derivatives, especially in the populations of Europe where the practice of using these antimalarials was not so common as in Asia and Africa. The reported case exemplifies possible ocular side effects in patients on long-term use of chloroquine (Delagil).
Keywords: chloroquine maculopathy; case; diagnosis; treatment; mistakes